IN VIVO EVALUATION OF CHITOSAN–TRICALCIUM PHOSPHATE BIOACTIVE COATING FOR ENHANCED OSSEOINTEGRATION OF TITANIUM DENTAL IMPLANTS - Ачилова Н.Г (TADQIQOTLAR, 2026)
Abstract The increasing prevalence of partial and complete edentulism necessitates the development of advanced implant systems capable of improving osseointegration and long-term clinical outcomes. Surface modification of titanium implants using bioactive materials represents a promising strategy for enhancing biological integration.This study aimed to experimentally evaluate the osteointegrative effectiveness and biocompatibility of a novel bioactive coating based on tricalcium phosphate and chitosan for domestically manufactured dental implants.An in vivo experimental study was conducted using 72 chinchilla rabbits divided into three groups: commercial implants, uncoated domestic titanium implants, and domestic implants coated with a bioactive polymer matrix. Radiological, densitometric, histomorphological, and biochemical analyses were performed at different postoperative periods.The developed coating demonstrated nanoscale morphology and stable adhesion to titanium surfaces. Experimental implants with bioactive coating exhibited accelerated bone regeneration, increased peri-implant bone density, and improved trabecular organization compared with uncoated implants. Positive osteointegration dynamics became evident after the first postoperative month.